2015
DOI: 10.1007/978-3-319-20282-2_5
|View full text |Cite
|
Sign up to set email alerts
|

Layout Planning Problems in Health Care

Abstract: In general, layout planning problems can be classified as in-house location problems where the aim is to minimize traveling or material handling costs based on distances by deciding on the relative positions of any kind of organizational units inside a building. This class of operations research problems originates from industrial applications, for example, planning the location of different machines of an assembly line needed to manufacture a product or the arrangement of racks and shelves within a warehouse.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Construction of new or renovation of existing health centers requires a large budget and a long time. Therefore, layout planning is a critical task as layout designs must be developed based on a well-studied strategic plan while considering the effect on customer experience and service quality; confusing layouts can add to customer' anxiety [38][39][40][41][42][43][44][45][46]. The team used a combination of the Process (functionality) layout, cellular manufacturing, and cellular layout.…”
Section: Methodsmentioning
confidence: 99%
“…Construction of new or renovation of existing health centers requires a large budget and a long time. Therefore, layout planning is a critical task as layout designs must be developed based on a well-studied strategic plan while considering the effect on customer experience and service quality; confusing layouts can add to customer' anxiety [38][39][40][41][42][43][44][45][46]. The team used a combination of the Process (functionality) layout, cellular manufacturing, and cellular layout.…”
Section: Methodsmentioning
confidence: 99%
“…In a similar study, Arnolds & Nickel, (2015) solved the hospital layout planning problem through the application of location analysis in Mexico's tertiary hospitals. A study of medical facility resource scheduling principles in Tanzania (Ileri 2013;Huyen, et al, 2017) showed that resource management is an integral part of healthcare management (Reiling, B., Ronda, D., & Murphy, M., 2021).…”
Section: Facility Location and Layout Decision In Healthcarementioning
confidence: 99%
“…Works in this category varied in scope. While Arnolds and Nickel (2015) addressed problems in all hospital areas, others focused on specific sectors such as operating rooms (Brogmus, Leone, Butler, & Hernandez, 2007), nursing units (Doede, Trinkoff, & Gurses, 2018;Rashid, 2015), and intensive care units (ICUs; Rashid, 2014). Brogmus, Leone, Butler, and Hernandez (2007) reviewed best practices in operating rooms, suggesting that good designs prevented accidents and improved the performance of doctors and nurses.…”
Section: Concepts and Guidelinesmentioning
confidence: 99%